Association of ACEI/ARB, inflammatory cytokines, and antiviral drugs with liver dysfunction in patients with hypertension and COVID-19 - Dong Xiang; Xiuhua Ren; Qian Chen; Hengyi Yu; Xiping Li; Dong Liu (Clinical and Experimental Hypertension, 2021)
Background: Currently, SARS-CoV-2 liver invasion, inflammatory cytokines, and antiviral drugs are widely thought to be associated with liver dysfunction in COVID-19 patients. Besides, previous studies indicated that ACEI/ARB drugs can increase the expression of hepatic ACE2, a cell entry receptor for SARS-CoV-2. This study aims to investigate whether ACEI/ARB aggravates liver injury and the association of inflammatory cytokines and antiviral drugs with liver dysfunction in patients with hypertension and COVID-19.Method: This retrospective study included 127 hypertensive patients with long-term use or nonuse of ACEI/ARBs hospitalized for COVID-19 from January 30 to April 7, 2020, in Tongji hospital of Wuhan, China. Demographic, clinical, laboratory, treatment, and outcome data were collected.Results: Of the 127 patients with COVID-19 and hypertension, 43 taking long-term of ACEI/ARBs and 84 without using ACEI/ARBs. Abnormal liver function was observed in part of ACEI/ARB and non-ACEI/ARB users but without significant differences between these two groups. Serum inflammatory cytokines, IL-6, IL-8, and TNFα, as well as inflammation-related markers, ferritin, procalcitonin, and C-reactive protein, were significantly elevated in patients with liver dysfunction. IL-6 level was positively correlated with liver function tests on admission and highly consistent with the changes of abnormal ALT, AST, and GGT during hospitalization, but the correlations of other inflammatory cytokines were low. There was no significant association between the use of antiviral drugs and liver dysfunction in these patients.Conclusion: The elevation of inflammatory cytokine, IL-6, but not ACEI/ARB and antiviral drugs, is closely associated with liver dysfunction in patients with hypertension and COVID-19.